Comparing Cancellous Bone Volume of the Manubrium to Iliac Crest in Fresh Cadavers. (1st February 2017) - Smith, Aaron; Kortebein, Sarah; Eid, Anas; Boughter, John; Cary, Nathan; Brooks, Jeffrey; Sebelik, Merry
Abstract : Objective: The iliac crest is the gold standard for cancellous bone grafting. This site is distant from head and neck reconstruction and may lead to significant postoperative morbidity. We propose an alternative harvest site within the head and neck with potentially less mobility deficits, the manubrium. Study Design: Fresh‐frozen cadaveric study. Setting: Gross anatomy laboratory. Subjects and Methods: Access to 18 cadavers was granted from the Medical Education and Research Institute in Memphis, Tennessee. The anterior iliac crests were exposed and H‐type osteotomies performed. The manubrium was accessed through a substernal notch incision and a cortical window created through the anterior manubrium. Cancellous bone was harvested from these sites. Cadaveric demographics and noncompressed and compressed volumes were recorded with statistical comparisons. Results: The population was predominantly male (12/18) with a mean age of 69.6 (95% confidence interval [CI], 64.0‐75.3) years. The mean body mass index was 22.9 (95% CI, 18.8‐27.1) kg/m 2 with no sex propensity. Uncompressed volumes did not vary, ranging from 6.4 to 7.5 mL. Compressed volumes (mL) for the right iliac crest (4.3; 95% CI, 3.0‐5.6), left iliac crest (3.5; 95% CI, 2.7‐4.2), and manubrium (2.4; 95% CI, 1.8‐3.0) varied (1‐way analysis of variance: F (2, 51) = 4.63; P <. 02). Furthermore, there was correlation between compressed volumes taken from either area ( r = 0.58; P <. 02). Conclusions: The manubrium can be used for cancellous bone grafting. This site affords a proximity to the head and neck rather than the distant iliac crest but with slightly lower yields. Potential applications include reconstructing small mandibular defects, mandible nonunion, or alveolar bone grafting.